Pengaruh Edukasi Kesehatan Terhadap Peningkatan Pengetahuan dan Perubahan Sikap Ibu Hamil di BPM Bina Marsasi Pada Tahun 2025 - Sari, Junawalia Mayang (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aimed to determine the effect of health education on improving pregnant women’s knowledge and attitudes regarding danger signs of pregnancy at BPM Bdn. Bina Marsasi, SST., M.Bmd in 2025. This research used a pre-experimental design with a One Group Pretest-Posttest approach. A total of 30 pregnant women were selected using purposive sampling. Health education was provided through lectures, interactive discussions, and leaflets. Data were collected using a structured questionnaire and analyzed using the Paired Sample t-Test. The average knowledge score increased from 58.67 to 82.33 and the attitude score from 61.00 to 78.00. The Paired Sample t-Test showed a significance value of 0.000 (p 0.05), indicating a statistically significant difference before and after education. Health education is effective in improving pregnant women's knowledge and attitudes regarding danger signs of pregnancy. It is recommended to be implemented regularly in antenatal care services.